Tingkat Desertifikasi Ekosistem Karst Di Kecamatan Darul Imarah Kabupaten Aceh Besar - Donny Avrilan; Kiman Siregar*; Suhendrayatna Suhendrayatna (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
The research has been carried out to assess the rate of desertification of the karst ecosystem regarding land damage in the Darul Imarah, Aceh Besar District. This study aims to determine the level of damage to the karst ecosystem and its effect on water quality and to determine the condition of land cover in the Mata Ie karst ecosystem., Aceh Besar District. The data collection method used is using Landsat 8 satellite imagery to assess the level of damage to the karst ecosystem area. The assessment of water quality and quantity was carried out by means of a direct survey in the Mata Ie karts ecosystem area by analyzing BOD, COD, TDS, Turbidity, DO, Temperature and pH. The results of the assessment of the level of damage to the kart ecosystem area of the Mata Ie area have changed. The results of the study prove that due to land clearing for plantation activities in the Mata Ie area and also as a tourist spot, the conditions in the area are not desertification, Karst area which consists of desertification types, namely karst vegetation cover of 75% so it is referred to as non-desertification while rock outcrop of 5.79% is also not desertified